Using Gender Inequality to Predict the Rate of African Women Entrepreneurship - Udanoh, Michael Uche; Zouria, Ayoub (International Journal of Emerging Trends in Social Sciences, 2018)
Entrepreneurship has been closely linked to the economic development of countries. The level of contribution that entrepreneurial activity has on an economy is dependent on factors such as competency, gender composition, and the type and level of developed entrepreneurship. Gender equality and female entrepreneurial activity are closely associated with the economic development of a country. In past research, it has been noted there is a negative association between the level of national income and the rate of female entrepreneurial development rate. The study investigates the association between gender inequality and the rate of women entrepreneurial development for twelve African countries. It uses gender-related variables and indices drawn from internationals databases to analyze the relationship they have to women entrepreneurial activity. Data from Global Entrepreneurship Monitor (GEM) on different stages of African women entrepreneurship development was used in the research.